Expression and promotor hypermethylation of miR-34a in the various histological subtypes of ovarian cancer - Schmid, Gabriel; Altevogt, Peter (BMC cancer, 2016)
Background: An increasing body of evidence shows that miR-34 family has tumor suppressive properties mediating apoptosis, cell cycle arrest and senescence. In ovarian cancer, miR34 family members were found to be under expressed. Particularly miR-34a has been revealed to be a direct transcriptional target of p53 which is frequently mutated in epithelial ovarian carcinomas especially in high grade serous cancer. Moreover, methylation of miR-34a CpG Islands was found to down-regulate miR-34a expression. The aim of this study was to investigate the clinical relevance of mir34a as well as its promoter methylation in a subset of 133 ovarian cancers with a special focus on the p53 mutation status, the dualistic type I and type II ovarian cancer model and the different histotypes. Methods: One hundred thirty-three epithelial ovarian cancers and 8 samples of healthy ovarian surface epithelium were retrospectively analysed for miR-34a expression with quantitative real-time reverse transcription PCR (qRT-PCR). Gene-specific DNA methylation was evaluated with MethyLight technique. Results: Significantly lower miR-34a expression was found in ovarian cancers than in healthy ovarian epithelium (p = 0.002). The expression of miR-34a was found lower in type II than in type I cancers (p = 0.037), in p53 mutated as compared to p53 wild type cancers (p = 0.003) and in high grade compared to in low grade cancers (p = 0.028). In multivariate COX regression model low expressing miR-34a cancers exhibited a reduced PFS (p = 0.039) and OS (p = 0.018). In serous cancers low miR-34a levels showed a worse OS confirmed also in multivariate analysis (p = 0.022). miR-34a promoter methylation was found higher in type II cancers than in type I (p = 0.006). mir34a expression and promoter methylation showed an inverse correlation in cancer samples (p = 0.05). Conclusion: We demonstrated a clinical independent role of miR-34a in epithelial ovarian cancers. Moreover, we corroborated the correlation between miR-34a expression and its promoter methylation in a large set of ovarian cancers. The inverse association between miR-34a expression and grading, p53 mutation status and dualistic tumor type classification, together with its prognostic relevance may underline the tumor-suppressive character of miR-34a in ovarian cancer.